2020
DOI: 10.1088/1755-1315/410/1/012095
|View full text |Cite
|
Sign up to set email alerts
|

Thermal comfort and Indoor Air Quality assessment in university classrooms

Abstract: Investigation of thermal comfort in various types of buildings is a rather intense research activity by recent years. Besides thermal comfort, the Indoor Air Quality (IAQ) is also important for the sensation of humans in indoor environments, as well as for their health. In the proposed work, a systematic measurement campaign in university classrooms in the Educational School of the University of Western Macedonia, Florina, Greece, is presented; the campaign was performed through winter time, noting that the Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…The impact of different ventilation modes on thermal comfort and CO 2 levels was also evaluated [27,69,124], as well as the relation between IAQ and thermal comfort [2]. In some cases, the concentration of other pollutants, such as VOCs, NO 2 , and CO was measured and correlated to the outdoor conditions [125][126][127]. The subjective perception of air quality was correlated to the environmental conditions, which showed that the perceived environmental quality was highly correlated to parameters, such as air temperature and ventilation rates [6].…”
Section: Indoor Air Quality and Thermal Comfortmentioning
confidence: 99%
“…The impact of different ventilation modes on thermal comfort and CO 2 levels was also evaluated [27,69,124], as well as the relation between IAQ and thermal comfort [2]. In some cases, the concentration of other pollutants, such as VOCs, NO 2 , and CO was measured and correlated to the outdoor conditions [125][126][127]. The subjective perception of air quality was correlated to the environmental conditions, which showed that the perceived environmental quality was highly correlated to parameters, such as air temperature and ventilation rates [6].…”
Section: Indoor Air Quality and Thermal Comfortmentioning
confidence: 99%
“…The impact of different ventilation modes on thermal comfort and CO 2 levels was also evaluated [27,69,124], as well as the relation between IAQ and thermal comfort [2]. In some cases, the concentration of other pollutants, such as VOCs, NO 2 , and CO was measured and correlated to the outdoor conditions [125][126][127]. The subjective perception of air quality was correlated to the environmental conditions, which showed that the perceived environmental quality was highly correlated to parameters, such as air temperature and ventilation rates [6].…”
Section: Indoor Air Quality and Thermal Comfortmentioning
confidence: 99%
“…In addition to the above, occupancy is also a crucial parameter affecting IAQ. High occupancy can lead to high levels of CO 2 concentration [28] as well as to the increase of VOCs due to secondary reactions between ozone and constituents of skin lipids [29,30].…”
Section: Introductionmentioning
confidence: 99%